Needs Analysis: Developing a Digital Literacy Integrated Speaking Syllabus for Arabic Pre-Service Teachers in China - Gu, Bingxin; Ismail , Zawawi Bin; Siraj , Saedah Binti (Journal of Ecohumanism, 2024)
Integrating digital literacy into language teacher preparation programs has gained increasing attention in recent years. With the expanding economic trade with Arab countries, Arabic language education is becoming more important in China. This study aims to identify the needs for developing a digital literacy-integrated speaking syllabus for Arabic pre-service teachers in China. The study presents phase 1: needs analysis of the design and developmental research (DDR) approach. Interviews were conducted to collect data. The finding shows that while digital literacy elements are integrated into the existing speaking syllabus through resources and multimedia presentation teaching approach, it is mainly concentrated on the skill domain rather than the knowledge and attitude domains. The study further found that the challenges for Arabic lecturers to integrate digital literacy are the lack of digital teaching resources, the lack of digital literacy training for lecturers, the heavy teaching tasks but limited class instructional time, and the restrictions of higher education institutional policies. Moreover, Arabic pre-service teachers have basic digital literacy skills for daily use but lack technical knowledge in Arabic and awareness of digital literacy. The results of the study provide valuable insights for curriculum designers and educators for language teacher education programs in China.